Monetary transmission during low interest rate environment in a dual banking system: evidence from Malaysia - Asbeig, Hussam; Kassim, Salina (Taylor & Francis, 2015)
This study aims to determine the role of bank loans in the transmission of monetary policy in an environment of low interest rate in the context of a dual banking system in Malaysia. By adopting a balanced panel data approach applied on data covering the period from 2000 to 2011, the study finds that changes in the monetary policy have no significant impact on the level of financing extended by the Islamic and conventional banks. However, bank-specific factors, namely size and liquidity play an important role in influencing the lending behaviour of both the Islamic and conventional banks, whereas capitalization is relevant only for the Islamic banks. Findings of the study provide important input for effective monetary policy implementation in countries with increasing presence of the Islamic banks.